Pengaruh Murottal Al-Qur’an Terhadap Intensitas Nyeri Disminore Pada Remaja Putri di SMK Kesehatan Kader Bangsa Palembang Tahun 2025 - Enjelina, Ria; Rahayu, Sri (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Prevalence of Dysmenorrhea According to data from the World Health Organization (WHO), there are 1,769,425 people (90%) women who experience dysmenorrhea with 10-15% experiencing severe dysmenorrhea. This study aims to determine the effect of murottal al-Qur'an on the intensity of dysmenorrhea pain in adolescent girls. This type of research is Quasi Experiment with a pretest-posttest research method design. The population in this study were all adolescent girls who experienced dysmenorrhea pain who met the inclusion criteria of the researcher, with a sample of 15 respondents of murottal al-Qur'an, the sampling technique used was purposive sampling. The research instrument used the NRS (Numeric Rating Scale) checklist sheet. Data analysis used the Independent T-Test and Paired T Test. The results of the analysis of Murrotal Al-Qur'an Therapy with a sig value of 0.002, meaning that it has significant effectiveness on the intensity of pain in adolescent girls. The results of the Independent T-Test showed a p-value of 0.878, meaning that Al-Quran murrotal therapy can reduce the intensity of dysmenorrhea pain in female adolescents at the Palembang Kader Bangsa Health Vocational School in 2025.